Analisis Karakteristik Papan Kayu Sawit Sebagai Alternatif Papan Furnitur - Dwianda, Yudi (Politeknik Kampar, 2025)
Palm oil is an industrial crop which generally enters its unproductive age at the age of 21 and must be cut down at the age of 25. But there are also those who, at the age of 16, are no longer productive due to various factors, such as seeds or infertile soil. The stems of this oil palm plant are considered as waste and are usually used only as compost. This study attempts to analyze the characteristics of palm wood planks and compare them with the boards commonly used for making furniture in UMKM. In this case the furniture board used as a comparison is the meranti board. Meranti wood is classified as class IV wood. From the results of the study using the ASTM D638 standard for tensile testing, it was found that the strength of palm wood aged 16-20 years was 4.47 MPa, palm wood aged 21-25 years was 14.41 MPa and Meranti wood was 56.58 MPa. The SNI 03-3958-1995 standard for compression testing obtained the compressive strength of 16-20 year old palm wood of 9.93 MPa, 10.05 MPa of 21-25 year old palm wood and 24.86 MPa of Meranti wood. Standard SNI 03-3959-1995 for flexure testing showed that the strength of palm wood aged 16-20 years was 4.50 N/mm2, palm wood aged 21-25 years was 21.17 N/mm2 and meranti wood was 28.13 N/mm2.